The Development of Lecture Schedule System in Politeknik Harapan Bangsa Surakarta: Pengembangan Sistem Jadwal Perkuliahan di Politeknik Harapan Bangsa Surakarta - Rohmawati, Dewi; Pantjarani, Ari; Naury, Chairullah (RADIANT: Journal of Applied, Social, and Education Studies, 2023)
Politeknik Harapan Bangsa Surakarta (Polhas) is one of the colleges in Surakarta city. This college has lecturer and staff to help the students. The duties of this staff are to arrange the classes schedule and the duties of the lecturer is carrying out the learning require a schedule to be able and find out what courses are taught. This college are required to have a Lecture Schedule System in addition to avoid collisions between teaching hour and lecture room. Another reason is to regulate learning and run effectively and efficient. Polhas has an online lecture schedule system but there are several features that must be improved, added, and removed to the system. Finally, the college can reuse the system as much as possible. Based in the background study the researcher finds the formulation of the problem is How to develop a classes schedule for Polhas which originally already exist and can be used by the campus with the latest feature. The limitations of the problem made by the researcher in the form of room classes and hour, parties in needed (admin, lecture and student) and a system made by online. To develop the schedule lecturer is using the PHP programming language and SQL database.